Strategies for the prevention of periodontal disease and its impact on general health in Latin America. Section III: Prevention - Andrés Duque Duque; Zilson Malheiros; Bernal Stewart; Hugo Jorge Romanelli (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract: Dental plaque removal and the understanding of risk factors, risk indicators and social determinants are important components in the prevention of periodontal disease. Periodontal diseases and dental caries are largely preventable conditions, but require a "common risk factor approach" with non-communicable diseases with the purpose of improving their prevention and control, and positive impact on health. The aim of this consensus was to identify the evidence and gaps in periodontal prevention in Latin American, and to propose individual and collective recommendations for the population, health professionals, dental practice and government. The prevention of periodontal diseases in Latin America has mainly been focused on oral hygiene instruction, use of toothbrushes and interproximal devices, but in some patients, it is necessary to use adjuncts to these measures, such as antimicrobial and/or probiotic products that are backed by broad scientific evidence. Some evidence has shown that there are inadequate knowledge, attitudes and practices among patients, dentist and other health professionals. The prevention of periodontal diseases and caries should be adopted as a healthy lifestyle routine, because of their local and systemic effects. Recently, new empowerment strategies have been proposed in order to generate behavioral changes. Periodontal diseases can often be prevented, or controlled by joined efforts between government health systems, scientific associations, universities, health professionals, private companies and communities. In conclusion, the relations between periodontal diseases, caries, healthy lifestyles and NCD's offer an ideal opportunity to change Latin American prevention strategies at both the individual level and population levels.